Pengaruh Pelatihan, Komunikasi dan Disiplin Kerja Terhadap Kinerja Karyawan (Literature Review Manajemen Kinerja) - Pratiwi, Dyah; Fauzi, Achmad; Febrianti, Berliana; Noviyanti, Diana; Permatasari, Evi; Rahmah, Nurul (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Previous research or related (relevant) research is very important in a research or scientific article. Previous research or relevant research helps to support/strengthen theories and phenomena of the relationship or influence between variables. This article reviews the Factors that influence Employee Performance, namely: Training, Communication and Work Discipline, a study of Performance Management literature. The purpose of writing this article is to build hypotheses about the influence of variables to be used in further research. The results obtained in this literature review article are: 1) Training has an effect on Employee Performance; 2) Communication has an effect on Employee Performance; and 3) Work Discipline affects Employee Performance.